2015
DOI: 10.1093/jxb/erv201
|View full text |Cite
|
Sign up to set email alerts
|

E151 (sym15), a pleiotropic mutant of pea (Pisum sativum L.), displays low nodule number, enhanced mycorrhizae, delayed lateral root emergence, and high root cytokinin levels

Abstract: HighlightThe phenotype of the E151 pea mutant, unique among known legume mutants, provides the first evidence for a promoting role for cytokinins in the development of the mycorrhizal symbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 54 publications
6
25
0
Order By: Relevance
“…truncatula (Truong et al, 2014) and Pisum sativum (Jones et al, 2015), where arbuscule proliferation appears analogous to what we have observed upon CO treatment. A few hypotheses can be made to explain this, each of which deserves further investigation.…”
Section: Exogenous Co Application Promotes Am Developmentsupporting
confidence: 87%
“…truncatula (Truong et al, 2014) and Pisum sativum (Jones et al, 2015), where arbuscule proliferation appears analogous to what we have observed upon CO treatment. A few hypotheses can be made to explain this, each of which deserves further investigation.…”
Section: Exogenous Co Application Promotes Am Developmentsupporting
confidence: 87%
“…Given that CK signaling plays a key role in nodule organogenesis, 12 and in lateral root formation, 17,18 we decided to identify which, if any, steps of CK biosynthesis were impacted by NF, by quantifying various forms of CK at 5, 10 and 16 d after the beginning of the treatments, following the protocol described by others. [19][20][21] Total CK content was decreased by drought in all tissues, although higher in nodules than in roots, which is in agreement with studies in soybean 22 or in other species. [23][24][25] When NF was applied under water stress conditions, CK content increased as soon as 5 d after the treatment in all plant organs (leaves, roots and nodules) till the end of the experiment (Fig.…”
supporting
confidence: 91%
“…Several pea symbiotic mutants have their ITs halted within the epidermal cell base. Pssym16 ( Guinel and Sloetjes, 2000 ) and Pssym15 ( Jones et al, 2015 ) are two such mutants; they are also known to accumulate cytokinins ( Table 1 ). Interestingly, Mtcre1 ( Gonzalez-Rizzo et al, 2006 ) and Ljhit1-1 ( Murray et al, 2007 ), two mutants defective in cytokinin sensing, have a majority of their ITs also blocked in the epidermis.…”
Section: Nodulation and Ethylenementioning
confidence: 99%